Scientific Validation of Ethnomedicinal Use of Ipomoea batatas L. Lam. as Aphrodisiac and Gonadoprotective Agent against Bisphenol A Induced Testicular Toxicity in Male Sprague Dawley Rats. (14th April 2019) - Majid, Muhammad; Ijaz, Fatima; Baig, Muhammad Waleed; Nasir, Bakht; Khan, Muhammad Rashid; Haq, Ihsan-ul
Abstract : Sweet potato ( Ipomoea batatas L. Lam.), known as "Shakarqandi" in Pakistan, is an imperative root vegetable with large size, traditionally used as aphrodisiac, antiprostatic, anti-inflammatory, antidiabetic, cardiotonic, and anticancer agent. Present study was conducted to gauge aphrodisiac potential of Ipomoea batatas ethyl acetate (IPT-EA, IPA-EA) and methanol (IPT-M, IPA-M) extracts from tuber and aerial part, respectively, via behavioral and biochemical tests and their possible protective role in BPA-induced gonadotoxicity at the dose 300 mg/kg in male Sprague Dawley rats. Phytochemical analysis was done qualitatively and quantitatively through total phenolic and flavonoid content (TPC and TFC) and high performance liquid chromatographic (HPLC-DAD) fingerprinting while antioxidant profiling used multimode in vitro assays. To calculate sexual excitement mount latency, intromission latency, mount frequency, intromission frequency, ejaculatory latency, and postejaculatory interval were examined while for biochemical ratification semen characteristics, levels of testosterone, follicle stimulating hormone (FSH), luteinizing hormone (LH), and estradiol were measured. Gonadoprotective ability was assessed through comet assay and histomorphological examination of testes. Qualitative analysis ensured the presence of phenols, flavonoids, tannins, anthocyanin, saponins, coumarins, terpenoids, and betacyanin. Quantitatively maximal TPC (304.32±7.20 μ g GAE/mg dry extract) and TFC (214.77±4.09 μ g QE/mg DE) were estimated in IPA-EA extract. IPT-EA yielded maximum rutin (7.3±0.12) and myricetin (2.7±0.14 μ g/mg DE) while IPA-EA and IPA-M yielded maximum caffeic acid (4.05±0.22 and 1.92±0.17 μ g/mg DE, respectively) in HPLC-DAD analysis. Extracts enhanced sexual excitement, improved semen quality, levels of testosterone, FSH, LH, and estradiol, and successfully attenuated toxic effects of BPA. Levels of endogenous antioxidant enzymes (CAT, SOD, POD, and GSH) were restored and NO abundance was minimized. Significant stimulation in sexual behavior, amelioration of toxicity symptoms, elevated spermatic production, raised viability, vitalized levels of gonadal hormones, maintained endogenous enzymes, genoprotection, and reformed testicular histology endorsed I. batatas as a better aphrodisiac alternative and gonadoprotective agent.